A gathering at the Institute for Global Leadership and the Top of the Hill Tribute/Illumination Ceremony at Goddard Chapel during the 2005 Commencement weekend. Photo 0016 - Sobecki, Nicki (Tufts Archival Research Center, 2008)
A gathering at the Institute for Global Leadership and the Top of the Hill Tribute/Illumination Ceremony at Goddard Chapel during the 2005 Commencement weekend.